Malaysia - Insurance Core Principles : Detailed Assessment of Observance - World Bank (Washington, DC, 2014)
This assessment provides an understanding of the significant regulatory and supervisory framework for the insurance sector of Malaysia. The assessment was conducted by Mark Causevic (external expert from OSFI Canada) during April 2012. Malaysia is undertaking the Financial Sector Assessment Program (FSAP) for the first time, and it includes a formal assessment of its observance with the Insurance Core Principles (ICPs) issued by the International Association of Insurance Supervisors (IAIS). The Malaysia market has been growing for Islamic insurance products (family takaful, general takaful, and re-takaful). The ICPs were not specifically developed with Islamic insurance products in mind. Consequently, based on the scope that was agreed upon prior to the start of the assessment work, details on the regulation, supervision and various workings of Malaysian Islamic insurance market are included in this report, but they do not form part of the ICP assessment ratings for Malaysia.